MENGURAI DETERMINAN SOSIAL TUBERKULOSIS DI NTB: PERSPEKTIF EPIDEMIOLOGI DAN SISTEM KESEHATAN - I Putu Artawan Prayoga; Nursini Juiban Hadi; Desak Gede Sri Baktiasih; Baiq Nirmalasari; Muhammad Munip; Yuly Peristiowati (Jurnal Cakrawala Ilmiah, 2025)
Objective: This article aims to analyze the social determinants contributing to the incidence of tuberculosis (TB) in West Nusa Tenggara (NTB) Province using an epidemiological and health systems approach. This study was conducted to understand how social, environmental, behavioral, and health service capacity factors interconnectedly influence the transmission and sustainability of TB cases in the region. Methods: This study employed a narrative literature review method through a search of Google Scholar, PubMed, DOAJ, ScienceDirect, and official reports such as the NTB Health Profile, Tuberculosis Information System (SITB), Riskesdas (Basic Health Research), and WHO documents. Literature was selected based on its relevance to the social determinants of TB, TB epidemiology in NTB, and environmental and health system risk factors over the past 10 years. The analysis was conducted using a narrative synthesis approach based on the Social Determinants of Health framework and infectious disease epidemiology theory. Results: The study indicates that TB in NTB is influenced by a combination of socioeconomic factors such as poverty, overcrowding, poor nutrition, poor sanitation, and substandard housing conditions. Behavioral determinants such as delayed self-examination, stigma, and irregular medication adherence contribute to worsening transmission. From a health system perspective, findings indicate challenges in case finding, accurate contact tracing, surveillance quality, and long-term treatment adherence. Geographic variation and disparities in access to services between Lombok and Sumbawa exacerbate epidemiological disparities and impact TB case detection outcomes in NTB. Implications: TB control in NTB requires a multisectoral approach that combines social interventions, residential environmental improvements, strengthening food security programs, health education, and strengthening the health system through increased primary care capacity, active surveillance, and community-based patient support. Integrating health policies with the housing, social, and education sectors is key to sustainable case reduction. Limitations: This study relies on secondary data that varies across sources and does not conduct statistical analysis or meta-analysis, so the strength of relationships between variables is not presented quantitatively.